THE IMPORTANCE AND METHODS OF IMPROVING INDEPENDENT LEARNING SKILLS AMONG STUDENTS OF SCHOOLS AND ACADEMIC LYCEUMS - Nizomova, Takhmina Jamoliddin qizi (INTERNATIONAL CONFERENCES, 2023)
Today, in our rapidly developing age, the role of science, continuous study, and, especially, independent research is extremely important. It is pivotal for each person to work independently on himself in order to achieve high results in every sphere of our life, to develop those spheres, and thereby serve society. Therefore, much research has been conducted by scientists and specialists in order to form autonomous learning skills among the young generation studying in schools and academic lyceums and to increase their interest in extracurricular studies. That is why new methods and techniques are being come up and implemented increasingly day by day. ‘In the organization of independent learning, preparing the ground for the mental development of students and forming critical and creative thinking in this process is considered a priority’[1].